Massive Pericardial Effusion and Tamponade Can Be a First Sign of Familial Mediterranean Fever. Issue 9 (September 2017) - Yoldaş, Tamer; Kayali, Şeyma; Ertuğrul, İlker and Doğan, Vehbi and Örün, Utku Arman and Karademir, Selmin
Abstract : Abstract: Cardiac involvement is a rare initial presentation of familial Mediterranean fever (FMF). We described 2 children with massive pericardial effusion and cardiac tamponade, who were later diagnosed as having FMF based on clinical and laboratory findings. Therefore, in children presenting with massive pericardial effusion, FMF should be considered as one of the differential diagnoses. In addition, massive pericardial effusion is a serious clinical condition that requires emergency therapeutic approach including pericardiocenthesis. For medical treatment, colchicine is the first line therapy, but in resistant cases, other anti-inflammatory drugs can be used for extra anti-inflammatory effect.